Vancomycin And Its Beta-Cyclodextrin Complex: Physicochemical Characterization And Its Cytotoxicity Evaluation On Human Glial Cell Line - SOFIAN, ZARIF MOHAMED (2011)
In this present study, the equimolar complexes of vancomycin, a broad-spectrum glycopeptide antibiotic with β-CD were prepared to evaluate their suitability for the development of a prolonged-release form of the antibiotic. β-CD/vancomycin complexes were prepared accordingly via freeze-drying and kneading techniques. The formation of the complexes was confirmed through X-ray Diffractometry (XRD), Thermogravimetric Analysis (TGA), Scanning Electron Microscopy (SEM) and Fourier Transfrom Infrared Spectroscopy (FT-IR). The results obtained were all in good agreement suggesting the successive formation of the aforementioned binary systems.